On the Dust Traces. Short Notes on the Material Power of the Almost-Nothing - Burgio , Gianluca (E|C, 2023)
Dust is considered a minor matter and has therefore always been placed on the lowest rung of the ladder of materiality. However, in a change of perspective, the world of neglected things (Puig de la Bellacasa 2011) takes on ontological relevance; this implies that dust - the main entity of neglected things - is reassembled in the system of spatial and social relations. In the contemporary world, the small, the fragile, the presque-rien (Dagognet) has been forgotten, and with it all the complexity of relationships. And yet, this formless and pulviscular mass, as matter, has an often underestimated power that is worth investigating; in fact, it is capable of enrolling human collectives, spaces and technical objects that participate together in its removal; its very existence generates practices of care and maintenance, as can be seen from the ethnographic investigation that is briefly described within the text.